Gambaran kecemasan dental anak berdasarkan usia pada siswa sekolah dasar negeri 2 karanganyar kabupaten indramayu - Fitriyasari, Rahmah; Dwimega, Arianne (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Oral and dental health is paramount due to its significant impact on an individual's quality of life. The prevalence of cavities in Indonesia is considerably high, with 57.6% of the population affected, but treatment is only sought by a mere 10.2%. In the Indramayu Regency of West Java, the limited access to dental care is attributed to the low number of dentists, which is a meagre 3%. The anxiety surrounding dental care often dissuade people, particularly children. Studies have highlighted the varying levels of anxiety in children. Purpose: This study aimed to determine the level of dental anxiety in students. Methods: Using a descriptive observational study with a cross-sectional design and a purposive sampling approach, we obtained 158 respondents who met the inclusion criteria. Data were taken using the Children Fear Survey Schedule-Dental Subscale (CSFSS-DS) questionnaire. Results: Dental anxiety levels were found in 142 (89.9%) children with low anxiety levels and about 16 (10.1%) children with high anxiety levels. There were 95 children aged 6-10 who had low anxiety and 8 child had high anxiety, then there were 47 children aged 11-13 years who had low anxiety, and 8 child had high anxiety. Conclusion: The level of dental anxiety is mainly dominated by children with mild dental anxiety (89.9%) and only a tiny percentage who have high dental anxiety (10.1%).